Hfq Regulates Efflux Pump Expression and Purine Metabolic Pathway to Increase Trimethoprim Resistance in Aeromonas veronii - Wang, Dan; Li, Hong; Ma, Xiang; Tang, Yanqiong; Tang, Hongqian; Huang, Dongyi; Lin, Min; Liu, Zhu (Frontiers in Microbiology, 2021)
Aeromonas veronii (A. veronii) is a zoonotic pathogen. It causes clinically a variety of diseases such as dysentery, bacteremia, and meningitis. And it also brings huge losses to aquaculture. A. veronii has been documented as a multiple antibiotic resistant bacterium. Hfq plays vital regulation roles in a variety of cell programs. The deletion of hfq in A. veronii showed an increased sensitivity to the trimethoprim, accompanying by the down regulation of the efflux pump related genes acrA and acrB in transcriptomic data. Coherently, the complementation of acrA and acrB in ∆hfq recovered the trimethoprim resistance. Besides, the productions of adenosine and guanosine were revealed to augment in ∆hfq in metabonomic data. Both wild type and ∆hfq conferred more sensitive to trimethoprim after appending 1mM adenosine or guanosine to M9 medium. These results demonstrated that Hfq mediated trimethoprim resistance by elevating efflux pump expression and degrading adenosine, and guanosine metabolites. Collectively, Hfq is a potential target to tackle trimethoprim resistance in A. veronii infection.